Strategi Pengembangan Kompetensi Digital Guru Dalam Meningkatkan Hasil Belajar Siswa Di Sekolah Menengah Atas Negeri 2 Luwu - Fitri Febrianti; Nurdin K; Hilal Mahmud (Hikamatzu | Journal of Multidisciplinary, 2025)
Students' creativity skills in schools have not yet been developed properly because the learning used is still conventional, The assignments given to students are in the cognitive domain. The purpose of this study was to determine the effectiveness of the PjBL model on student creativity through the creation of scrapbook media on the material of the body's defense system. Method: This research was conducted at SMA Negeri 1 Tukdana with a sample of 20 students in class XI MIPA 4. This type of quantitative research uses the Pre-Experimental Design used the type is One Shoot Case Study. The instrument used is an assessment of student product creativity and student response questionnaire. Results: Students' creativity in making scrapbook media products has an average value of 74.53% with a fairly creative category. Meanwhile, students' creativity in making scrapbook media products has an average value of 83.28% in the good category. Data in the experimental class from the assessment of student product creativity is normally distributed, obtained t-count=1.82 and ttable=1.73 because tcount>ttable, then Ho has rejected. Conclusion: the Pjbl model is effective in student creativity through the creation of scrapbook media on the material of the body's defense system at SMAN 1 Tukdana.